2020
DOI: 10.1002/mrd.23419
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of FSH‐regulated gene expression and histone modification in mouse granulosa cells

Abstract: Follicle-stimulating hormone (FSH) regulates ovarian follicular development through a specific gene expression program. We analyzed FSH-regulated transcriptome and histone modification in granulosa cells during follicular development. We used super-stimulated immature mice and collected granulosa cells before and 48 h after stimulation with equine chorionic gonadotropin (eCG). We profiled the transcriptome using RNA-sequencing (N = 3/time-point) and genome-wide trimethylation of lysine 4 of histone H3 (H3K4me3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…In this work, the effect of FSH on the expansion of cumulus cells, estradiol production, and oocyte nuclear maturation was observed ex vivo, thus reinforcing the seminal effects of this hormone on cellular hallmarks of oocyte maturation [32][33][34]. Cumulus cells mediate FSH signaling pathways that contribute to the acquisition of developmental competence [14,[35][36][37].…”
Section: Discussionmentioning
confidence: 55%
“…In this work, the effect of FSH on the expansion of cumulus cells, estradiol production, and oocyte nuclear maturation was observed ex vivo, thus reinforcing the seminal effects of this hormone on cellular hallmarks of oocyte maturation [32][33][34]. Cumulus cells mediate FSH signaling pathways that contribute to the acquisition of developmental competence [14,[35][36][37].…”
Section: Discussionmentioning
confidence: 55%
“…A more accurate determination of the number and function of FSH-regulated genes as well as LH-regulated genes have been reported over the years 15,16,61-63 and demonstrate the importance of functional studies during the later stages of follicular development to better coordinate the ovarian activity. In this regard, we have shown previously the suppression of JAK3 in vivo by endogenous LH or hCG injection in bovine species and identified JAK3 binding partners in GC using the yeast two-hybrid method 15,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the list of granulosa-specific genes included canonical marker genes HSD17B1, INHBB, FOXL2, and AMH and the recently reported TNNI3, MAGED2, CD99, SERPINE2, CDH2, and BEX1 (9, 13), along with many histone protein-coding genes (data S5), which have not been reported for granulosa cells. However, numerous studies have suggested that proliferating granulosa cells undergo large-scale epigenetic change during late folliculogenesis, partly driven by gonadotrophins such FSH (40)(41)(42)(43). The list also included genes involved in granulosa cell-oocyte signaling, such as the transzonal projection-related genes FSCN1 and MYO10, and the tetraspanin protein gene TSPAN7, which is involved in extracellular vesiclemediated signaling between granulosa cells and the oocyte (44,45).…”
Section: Discussionmentioning
confidence: 99%